Instructors’ and Students’ Perceptions of Clinical Evaluation Programmes of Nursing Colleges in Riyadh, Kingdom of Saudi Arabia - DAGAMSEH, MOHAMMAD SUHAIL (2024)
This study investigates the perceptions of clinical evaluation programmes (CEPs) among nursing students and instructors in Riyadh, Saudi Arabia, emphasizing the crucial role these programmes play in bridging the gap between theoretical knowledge and practical application in nursing education. Clinical evaluation is essential for preparing nursing students to meet the demands of real-world healthcare settings. Quantitative results from surveys involving 301 students and 69 instructors showed that students rated their satisfaction with CEPs at an average score of 3.26, while instructors gave them a slightly higher score of 3.50, indicating overall positive perceptions. Despite these positive scores, both students and instructors noted significant challenges in the current evaluation processes. Qualitative data, derived from semi-structured interviews, revealed concerns about the inconsistency of evaluation tools, the subjectivity of assessments, and the gap between the skills taught in the classroom and those required in clinical settings. Students often felt underprepared for real-world clinical situations, while instructors faced difficulties in ensuring fair and objective evaluations across different clinical environments. Both groups recommended the standardization of evaluation tools and methods, increased support and training for clinical instructors, and enhanced communication between instructors and students to ensure more reliable feedback and assessments. The study suggests that implementing evidence-based, standardized evaluation practices, alongside robust training programmes for clinical instructors, will enhance the effectiveness of CEPs and better prepare nursing graduates to meet the evolving challenges of the healthcare sector. Keywords: Clinical Evaluation Programmes (CEPs), Nursing Education, Perceptions of Students and Instructors.